The Determinants of Mobile Marketing Services Acceptance among Gen-Y Consumers - Ismail, Mohammad; Razak, Razli Che; Hakimin Yusoff, Mohd Nor; Wan Zulkiffli, Wan Farha; Wan Mohd Nasir, Wan Mohd Nazdrol (International Journal of Criminology and Sociology, 2022)
This research aims to examine the acceptance of mobile marketing services by computing the consumers’ intention towards actual use for mobile marketing services. This research’s conceptual framework is developed based on the Theory of Planned Behaviour by examining the attitude, subjective norms, perceived behavioural control, intention, and actual use. This research also strives to identify the effects of risk perception on purpose, which still an inadequacy of explanation in mobile marketing usage among Gen Y. A total of 650 questionnaires was distributed to the full-time university students of four Universities in the East Coast Region in Malaysia. The main statistical technique used in this research was SmartPLS and SPSS software. This research indicated that attitude, subjective norms, perceived behavioural control, and perceived risk tend to influence intention to use. The behavioural intention was also found to influence the actual use of mobile marketing services among generation Y. Based on the findings, the theoretical and practical implications of the study, limitation, and future studies suggestions were discussed in this research.